2022
DOI: 10.3389/fpubh.2022.1003791
|View full text |Cite
|
Sign up to set email alerts
|

Spatially varying associations between the built environment and older adults' propensity to walk

Abstract: Population aging has become a severe issue facing most nations and areas worldwide—with Hong Kong being no exception. For older adults, walking is among the most well-liked travel modes, boosting their overall health and wellbeing. Some studies have confirmed that the built environment has a significant (spatially fixed) influence on older adults' walking behavior. However, little consideration has been given to the potential spatial heterogeneity in such influences. Hence, this study extracted data on older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, it has been observed that older adults' physical and psychological aging leads to a preference for traffic facilities. Streets with high traffic volumes and uneven gradients tend to lower older adults' willingness to travel; older adults prefer to travel on streets that have better amenities and less traffic flow [49]. Older adults' physical states did not significantly influence their choice to travel at different times.…”
Section: Travel-perception Analysis For Different Travel Timesmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, it has been observed that older adults' physical and psychological aging leads to a preference for traffic facilities. Streets with high traffic volumes and uneven gradients tend to lower older adults' willingness to travel; older adults prefer to travel on streets that have better amenities and less traffic flow [49]. Older adults' physical states did not significantly influence their choice to travel at different times.…”
Section: Travel-perception Analysis For Different Travel Timesmentioning
confidence: 86%
“…A higher number of routes signifies enhanced access to destinations. Prior research showed that older adults generally preferred walking as their primary travel mode [49]. In metropolitan areas, more vehicles travel on primary and secondary roads, which can pose risks to older pedestrians.…”
Section: Analysis Of Constraints Between the Built Environment And Tr...mentioning
confidence: 99%
“…Previous studies have suggested that walking is the most popular mode of transportation for older adults, and benefits their overall health and well-being [ 17 , 54 , 55 ]. Furthermore, a survey of older adults in Chongqing showed that 67.3% walked to travel, and 78.9% travelled within a two-kilometre radius [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inequality of social service resources for disadvantaged groups has been a primary concern in sustainable urban development [ 15 , 16 ]. Researchers have grown more interested in EFC disparity in recent years [ 17 ]. Various methods have been used to assess public service equality, including spatial accessibility, Gini coefficient analysis, and spatial autocorrelation analysis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%